THE INFLUENCE OF WORK ENVIRONMENT ON WORK COMMITMENT AT THE REGIONAL DRINKING WATER COMPANY OF MAKASSAR CITY - Rifqi Wiratama Abdurrahman; Siti Hasbiah; Tenri SP Dipoatmodjo; Romansyah Sahabuddin; Uhud Darmawan Natsir (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyze the effect of work environment and non-physical work environment on the work commitment of employees of the general and staffing sections of the Makassar city drinking water regional company. This research uses quantitative methods with descriptive approaches and multiple linear regression analysis. The sampling technique used purposive sampling with a total of 40 employees. The data obtained were analyzed using the t test, F test and R-Square test to test the effect of physical environment variables and the non-physical environment on work commitment. The results show that the physical work environment and non-physical work environment have a significant positive effect on work commitment both partially and simultaneously. The t-count value for the physical work environment is 3.593 and the non-physical work environment is 2.901, both of which are greater than the t-table, with a significant value of 0.01 each, indicating a significant effect. Simultaneously, the physical work environment and non-physical work environment contribute greatly to work commitment. This research suggests the company to the importance of this aspect especially the physical work environment and non-physical work environment in order to increase work commitment especially in the general and staffing department.